Mock Jurors’ Perceptions of Child Sexual Abuse Cases: Investigating the Role of Delayed Disclosure and Relationship to the Perpetrator - Miller, Quincy C. (Journal of interpersonal violence, 2022)
Child sexual abuse (CSA) claims brought forward weeks, months, or years after the alleged events are commonplace, yet the trial-level ramifications of delayed disclosure remain unclear. In the present study, we investigated the influence of length of delayed disclosure (1 day, 1 month, 10 months) as a function of the victim-perpetrator relationship (next-door neighbor, stepfather) on mock jurors? perceptions of a CSA case. Jury-eligible participants (N = 328) read a mock trial summary describing an alleged incident of CSA between an adult male defendant and a seven-year-old female victim. Participants then rendered various case judgments. When length of delay was 10 months versus 1 day, mock jurors rendered fewer guilty verdicts and lower ratings of victim trustworthiness, believability, memory strength, and memory accuracy. Effects of length of delay varied as a function of the victim-perpetrator relationship, but only when the perpetrator was the victim?s next-door neighbor versus stepfather. When the perpetrator was the victim?s next-door neighbor, participants rated the likelihood of abuse as higher and the victim?s memory as stronger with shorter versus longer lengths of delay. Delay did not vary as a function of the victim-perpetrator relationship when the perpetrator was the victim?s stepfather. Findings have implications for trial-level safeguards (e.g., expert testimony) in CSA cases involving delayed disclosure.